2020
DOI: 10.3389/fimmu.2020.549319
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Cytokine Interleukin 15-Like (IL-15L) Induces a Type 2 Immune Response

Abstract: Related interleukin-2, -15, and -15-like (IL-2, -15, and -15L) are ancient cytokines, with all three genes surviving in extant fish and some mammals. The present study is the first to identify IL-15L functions, namely in rainbow trout. In isolated trout splenocytes, and in vivo, purified recombinant IL-15L+IL-15Rα molecules induced expression of IL-4 and IL-13 homologs, which are markers of type 2 immunity. In contrast, trout IL-15 stimulated type 1 immunity markers, thus IL-15 and IL-15L can have opposing fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 114 publications
(191 reference statements)
1
2
0
Order By: Relevance
“…Some of the DEGs that significantly overlapped between the SE and LE groups, notably in the gills, have key functions in mucosal defence, including il15rα, the putative receptor for IL-15. The roles of IL-15L and IL-15Rα in Type 2 immunity have recently been reported in fish [41], and this study points to the possibility that it may also be important in immunity to oxidative stress. In mammalian systems, the IL-15 myokine has been implicated to have a protective effect against H 2 O 2 -mediated oxidative stress [42].…”
Section: Discussionsupporting
confidence: 62%
“…Some of the DEGs that significantly overlapped between the SE and LE groups, notably in the gills, have key functions in mucosal defence, including il15rα, the putative receptor for IL-15. The roles of IL-15L and IL-15Rα in Type 2 immunity have recently been reported in fish [41], and this study points to the possibility that it may also be important in immunity to oxidative stress. In mammalian systems, the IL-15 myokine has been implicated to have a protective effect against H 2 O 2 -mediated oxidative stress [42].…”
Section: Discussionsupporting
confidence: 62%
“…In contrast to rainbow trout RBC, which were shown to express IL1β , IL8 and IFNγ in response to infectious hematopoietic necrosis virus (IHNV) and thermal stress, A. salmon RBC demonstrated high transcript levels of only IL15 and IL34 ( 7 , 36 ). Studies on the characterization of IL15 in rainbow trout suggested its involvement in CD4+ T cell survival, where it induces IFNγ through a STAT5p - dependent signaling pathway ( 60 , 61 ). The function of IL34 is modestly explored in salmonids.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the ability of IL-2 to act primarily as a soluble cytokine and of IL-15 as a heterodimer with IL-15Rα was already established in fish. Thus, IL-2, IL-15, IL-15Rα and the IL-15 transpresentation system evolved at least 460 million years ago, with a shared IL-15L between cattle and trout (Gunimaladevi, Savan, Sato, Yamaguchi, & Sakai, 2007;Wang, Holland, Carrington, Zou, & Secombes, 2007;Yamaguchi et al, 2020).…”
Section: Il-15rα Recycles and Presents Il-15 In Trans To Neighboring ...mentioning
confidence: 99%